Rachunek kosztów działań w obszarze marketingu - Bieńkowska, Agnieszka; Kral, Zygmunt; Zabłocka-Kluczka, Anna (Activity Based Costing in Marketing, 2006)
The purposefulness of the use of the activity based costing in marketing was justified. The essence of this system was presented. Stages of pointed costing method were listed and characterised. Advantages and conditions of using the ABC were pointed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 21-28